Estrategias didácticas constructivistas para la mejora del proceso enseñanza – aprendizaje de Ciencias Naturales. Año Lectivo 2023-2024 - Conza Jumbo, Mireya del Carmen (2024)
The implementation of constructivist didactic strategies in the development of the teaching-learning process generates significant learning and student participation in the construction of their own learning by facilitating the understanding of scientific content. In the case of this research, the objective is aimed at “To enhance the academic performance of eighth grade students of Basic General Education, through the implementation of constructivist didactic strategies, which generate the progressive construction of significant learning, as a result of the improvement of the teaching-learning process in the subject of Natural Sciences, in "Adolfo Valarezo" High school, academic year 2023 - 2024.”. To satisfy this objective used the inductive method, the approach is qualitative, to Participatory Action Research and the temporality it is transversal; through which and with the help of evaluation and research instruments it is determined that constructivist didactic strategies such as: experimentation, information organization, joint elaboration, gamification, among others, improve students' academic performance. It is concluded that the application of constructivist didactic strategies generates the construction of meaningful learning in students and in turn improves their academic performance. Key words: constructivist didactic strategies, significant learning, academic performance, participation, comprehension